Evidence mapping for decision making: feasibility versus accuracy – when to abandon high sensitivity in electronic searches - Buchberger, Barbara; Krabbe, Laura; Lux, Beate; Mattivi, Jessica Tajana (GMS German Medical Science, 2016)
Background: Mapping the evidence is a relatively new methodological approach and may be helpful for the development of research questions and decisions about their relevance and priority. However, the amount of data available today leads to challenges for scientists sometimes being confronted with literature searches retrieving over 30,000 results for screening. Objectives: We conducted an evidence mapping of the topic “diabetes and driving” to investigate its suitability for an evidence-based national clinical guideline. In addition, we compared a highly sensitive search with a highly specific one.Methods: Based on a systematic review, our database searches were limited to publications from 2002 to present in English and German language. Results: Due to the strongly focused topic and the limits, our sensitive search identified a manageable number of references including sufficient evidence to answer our research question. Using the specific search strategy, we achieved a reduction of citations by 25%, concurrently identifying 88% of relevant references.Conclusions: Evidence mapping with the intention of gaining an overview of a research field does not require high level accuracy in contrary to systematic reviews. Keeping this distinction in mind, a mass of extraneous information will be avoided by using specific instead of highly sensitive search strategies.